2022
DOI: 10.1002/erv.2908
|View full text |Cite
|
Sign up to set email alerts
|

The moderating role of sleep duration on momentary relations between negative affect and loss‐of‐control eating in children and adolescents

Abstract: Objective Loss‐of‐control (LOC) eating is associated with eating disorders and obesity, and thus it is imperative to understand its momentary risk factors in order to improve intervention efforts. Negative affect has been proposed as a momentary risk factor for LOC eating, but the evidence for its effects in children and adolescents is mixed. Short sleep duration (which is very common in youth), may be one variable that moderates the relation between negative affect and subsequent LOC eating. As such, we aimed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…Existing literature supports our finding that prenatal LOC relates to lower scores on sleep duration and nicotine use CVH metrics; prior research has found an increased prevalence of combustible tobacco and NDS use among individuals with diagnosed eating disorders, including binge eating disorder and bulimia nervosa (Morean & L’Insalata, 2018; M. Solmi et al, 2016), and some evidence suggests an association between LOC and poorer sleep (Allison et al, 2016; Manasse et al, 2022; Parker et al, 2022). Although previous research has shown associations between LOC and lower diet quality and higher BMI (Goldschmidt, 2017), we did not find associations between prenatal LOC and scores on these CVH metrics during pregnancy.…”
Section: Discussionsupporting
confidence: 86%
“…Existing literature supports our finding that prenatal LOC relates to lower scores on sleep duration and nicotine use CVH metrics; prior research has found an increased prevalence of combustible tobacco and NDS use among individuals with diagnosed eating disorders, including binge eating disorder and bulimia nervosa (Morean & L’Insalata, 2018; M. Solmi et al, 2016), and some evidence suggests an association between LOC and poorer sleep (Allison et al, 2016; Manasse et al, 2022; Parker et al, 2022). Although previous research has shown associations between LOC and lower diet quality and higher BMI (Goldschmidt, 2017), we did not find associations between prenatal LOC and scores on these CVH metrics during pregnancy.…”
Section: Discussionsupporting
confidence: 86%
“…However, the literature on sleep and disordered eating is still scarce. Supporting this idea, variations in sleep duration may affect the susceptibility to losing control over eating after experiencing negative affect in a young population, and variations in sleep duration may impact susceptibility to losing control over eating after experiencing negative feelings in a young population ( 64 ). Furthermore, chronic sleep restriction may increase the likelihood of suboptimal dietary behavior in adolescents with excess weight ( 65 ).…”
Section: Discussionmentioning
confidence: 99%